PENGEMBANGAN MEDIA KARTU FLASH CARD TERHADAP MATERI BANGUN DATAR DAN RUANG UNTUK MENINGKATKAN KEMAMPUAN BELAJAR SISWA - Yovita Dewi, Finansia; Darwin Effendi; Noviati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to develop and produce teaching material products in the form of flash card learning media for flat building materials and spaces to improve students' learning abilities which can be used by educators in the learning process. This research was carried out at SD Negeri 140 Palembang class V A. The development model used in this study is the ADDIE model, in the development of ADDIE, the data collection technique in this study uses interview data, questionnaires, tests, & documentation. The validity results consisted of material experts, media experts, and linguists who obtained 89.16% results with a very valid category. The feasibility results from educators obtained 96% results with a very feasible category. The difference between the learning outcomes of students who have not used the media with an average score of 34.5 and after using the media the average score obtained is 95. The effectiveness results obtained from the pretest and posttest were obtained with an N-Gain result of 0.91 with the category of very effective.